The Problem Faced by International Internship Students in Conducting Teaching Practices at Southern Thailand - Fatmawati, Fatmawati; Jabri, Umiyati; Samad, Ita Sarmita (Universitas Muhammadiyah Enrekang, 2022)
The international internship program was the topic of this research provides opportunities for students to be involved in community service conducted abroad. This research was qualitative by taking data from eight students who participated in this international internship program. The results of this study used a descriptive method. This study aims to analyze the problems faced and the solutions used by the intern students of the Muhammadiyah University of Enrekang batch 2. The results of this study indicate that there are 8 problems faced by interns, including administrative problems, health, psychological, culture shock, language barriers, teaching assignments, social, and available facilities. Apart from the problem, this research also includes the solutions used by the interns to solve these problems. With this research, it can be used as a reference or guideline for students who want to take part in international internships later